(untitled) (Journal of Partial Differential Equations, 2002)
This paper concerned with the classical solutions to system of one dimensional hydromagnetic dynamics with dissipative mechanism. Under certain hypotheses on the initial data, the global existence and the formation of singularities for classical solution are obtained. Our results show that the damping dissipation is strong enough to preserve the smoothness of the classical solution.